SASE COMPLIANCE FRAMEWORK: A COMPREHENSIVE GUIDE TO REGULATORY REQUIREMENTS AND IMPLEMENTATION STRATEGIES IN DISTRIBUTED NETWORKS - Namboodiri Arun Mullamangalath Kesavan (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The emergence of Secure Access Service Edge (SASE) represents a transformative advancement in network security and compliance management for distributed organizations. This comprehensive article framework integrates traditional network security functions with modern WAN capabilities, addressing the evolving challenges of cloud adoption, remote work, and digital transformation. The article examines the critical aspects of SASE implementation, including regulatory compliance across multiple jurisdictions, security component integration, and strategic deployment methodologies. Through article analysis of real-world implementations, the article demonstrates how organizations can effectively navigate complex regulatory requirements while maintaining operational efficiency. The investigation encompasses crucial elements such as Zero Trust Network Access, Data Loss Prevention, and AI-driven security controls, providing insights into their collective impact on organizational security posture. Furthermore, the article explores implementation strategies, challenges, and future considerations, offering a detailed roadmap for organizations undertaking SASE transformation. The findings highlight the importance of structured implementation approaches, comprehensive security controls, and automated compliance management in achieving successful SASE deployments across diverse organizational environments.